Polarization of homogeneous groups of territorial entities - S. Sh. Aslaeva (Управление)
The aim of the study is to assess the polarity and polarization of the economic development of territories by homogeneous groups. The object of the study is the economic space of the Republic of Bashkortostan. The subject of the research is the essence of polarity, polarization and leveling in the socio-economic development of territorial entities. The research methods are comparative, logical, statistical analysis, the analysis of structure and dynamics, graphical interpretation of the results. The author proposes an original method for assessing the polarity and polarization of the spatial development of the region. The method was tested on the example of municipalities of the Republic of Bashkortostan. The paper presents a graphical model of polarization and leveling of polarization by typological homogeneous groups of municipalities. Homogeneous groups are characterized by the presence of a significant relationship between indicators of macroeconomic dynamics, the content of internal structural interactions and dynamic changes in spatial structure. According to the types of polarization the author presents strategies for advancing and catching up development, strategies for equalizing with stagnation, the formation of a gap. The article shows optimal leveling limits. The author draws a conclusion, that among municipal districts of the same typological group, gaps are formed and further polarization occurs. The paper detects that, despite the difference between homogeneous groups of municipalities on the socio-economic level, the processes of polarization are similar for each indicator. The study concludes about a unified system of management policy in the region for all municipalities.